Extending Women's Entrepreneurship Research in New Directions - Hughes, Karen D.; Jennings, Jennifer E.; Brush, Candida; Carter, Sara; Welter, Friederike (Entrepreneurship Theory and Practice, 2012)
The dramatic expansion of scholarly interest and activity in the field of women's entrepreneurship within recent years has done much to correct the historical inattention paid to female entrepreneurs and their initiatives. Yet, as the field continues to develop and mature, there are increasingly strong calls for scholars to take their research in new directions. Within this introduction to the special issue, we expand upon the reasons for this call, describe who responded, and summarize the new frontiers explored within the work appearing in this and another related collection. We conclude by delineating new territories for researchers to explore, arguing that such endeavors will join those in this volume in not only addressing the criticisms raised to date, but also in generating a richer and more robust understanding of women's entrepreneurship.